Genomic and Experimental Analysis of the Biostimulant and Antagonistic Properties of Phytopathogens of Bacillus safensis and Bacillus siamensis - Fabiola Altimira; Sebastián Godoy; Matias Arias-Aravena; Bárbara Araya; Christian Montes; Jean Franco Castro; Elena Dardón; Edgar Montenegro; Wilson Pineda; Ignacio Viteri; Eduardo Tapia (Microorganisms, 2022)
The B. safensis RGM 2450 and B. siamensis RGM 2529 strains were isolated from the rhizosphere of plants presenting resilience to abiotic and biotic stress conditions. To understand the implications of bacteria in resilience, a genomic and experimental analysis was carried out on their biostimulant and phytopathogenic antagonist properties. Genome analyses of both strains indicated that they have the potential to synthesize bioactive compounds such as the battery of non-ribosomal peptides, polyketides, extracellular enzymes and phytohormones. These results were consistent with the antagonistic activities of both strains against the phytopathogens Botrytis cinerea, Colletotrichum acutatum, Fusarium oxysporum and Phytophtora cinnamomi. They also showed the capacity to solubilize phosphorus, fix nitrogen and produce indole acetic acid. This was observed in tomato seedlings grown from seeds inoculated with the mixture of strains which presented significantly greater length as well as wet and dry weight in comparison with the treatments individually inoculated with each strain and the control. Accordingly, the combination of B. safensis RGM 2450 and B. siamensis RGM 2529 showed synergistic biostimulant activity. These findings contribute new knowledge of the genomic and metabolomic properties taking part in the symbiotic interactions between these strains and the plants and uphold the combined use of both strains as a biostimulant.